Ketidaksesuaian Metode Pembelajaran dengan Tuntutan Implementasi Kurikulum Merdeka di Sekolah Menengah Pertama di Jepara - Putra, Nidhomun; Darnoto (JOM, 2024)
This study aims to identify and describe the challenges faced by teachers and students in implementing the Merdeka Curriculum at SMP Islam Pecangaan, as well as to explore the active learning strategies employed by teachers in accordance with the demands of the curriculum. This research adopts a qualitative method with a descriptive approach. Data were collected through observations, in-depth interviews, and documentation. The data sources include the principal, the vice principal for curriculum, teachers, and students at SMP Islam Pecangaan. The study found several issues in the implementation of the Merdeka Curriculum, including government policies perceived as overly coercive, limited school facilities and infrastructure, and a lack of teacher understanding of the new curriculum. Teachers encountered various inconsistencies in applying the curriculum, which affected the effectiveness of active learning in the classroom. These findings highlight significant challenges in the implementation of the Merdeka Curriculum, necessitating further evaluation of educational policies and teacher training strategies. This research also contributes to the literature on the implementation of new curricula and pedagogical adaptation in school environments.